PENGGUNAAN HAK KYIAR PADA AKAD MURABAHAH DITINJAU DARI FATWA DSN-MUI - Aulia Alwi (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2022)
Most of the provisions on Murabahah are contained in the fatwa of the National Sharia Council of the Indonesian Ulema Council (DSN MUI) as the National Sharia Council is an institution established to carry out the wishes of Muslims regarding the economy and promote the application of Islamic Sharia in the economic and financial fields. However, the provisions in MUI Fatwa No. 04/DSN-MUI/IV 2020 do not fully reflect the protection of customers. Therefore, researchers want to review MUI Fatwa No. 04/DSN-MUI/IV 2020 regarding murabahah transactions using the theory of kyiar rights. This type of research is library research. The results of the study suggest that the right of khiyar in the practice of murabahah contracts in Islamic banks should be applied in a maslahat manner for both parties, namely customers and Islamic banks so that transactions run well so that the value of the sharia value of Islamic banks is reflected in the willingness and pleasure of each party. In accordance with article 2 paragraphs 5 and 6 of DSN fatwa No. 04/DSN-MUI/IV/2000 concerning murabahah.